A clinical case of community-acquired pneumonia with severe obstructive respiratory failure syndrome caused by Chlamydia pneumoniae in an early-age child with a burdened premorbid background - R. M. Fayzullina; I. V. Kazakova; R. R. Gafurova; A. E. Chernyshova (Association of Paediatric Allergists and Immunologists of Russia (APAIR), 2023)
Introduction. Violation of bronchial patency is a particularly urgent problem in pediatric practice, which is primarily due to the increase in the frequency of its development and occurrence in young children with acute respiratory infections of the lower respiratory tract, the lack of an unambiguous and unified interpretation of the causal factors of formation and pathogenetic mechanisms, as well as the difficulty of differential diagnosis of pathological conditions accompanied by obstruction.Presentation of the clinical case. The publication presents a clinical case of community-acquired bilateral lower lobe pneumonia in combination with severe obstructive type respiratory failure syndrome caused by Chlamydia pneumoniaе in an early-age child with an established diagnosis of bronchial asthma: polyvalent sensitization, who suffered COVID-19 twice during the year. The severe course of the disease with pronounced clinical manifestations of intoxication and respiratory insufficiency of the obstructive type in the patient was accompanied by laboratory changes in clinical and biochemical blood tests, the presence of a diagnostic titer of antibodies to Chlamydia pneumoniaе during serological testing and a CT picture of multiple areas of lung tissue compaction according to the 'frosted glass' type, predominantly rounded, of varying length in the lower parts right and left lung. In our clinical case, the differential diagnosis of obstructive syndrome in a young child caused a number of difficulties due to the influence of factors of the patient's burdened premorbid background on its formation: the presence of a hereditary predisposition to maternal atopy (bronchial asthma) and verified diagnoses of bronchial asthma and atopic dermatitis: sensitization to birch pollen, cow's milk protein and chicken yolk eggs; episodes of acute urticaria.Conclusion. During a comprehensive clinical and laboratory-instrumental examination conducted in a hospital, the patient was diagnosed with: 'Community-acquired bilateral lower lobe pneumonia caused by Chlamydia pneumoniaе, severe, acute, uncomplicated, DN II-III obstructive type.'